Clinical Profile and Pattern of Uveitis in a Tertiary Care Centre - Hemant Singh Trehan, Anuradha Singh, Raji Kurumkattil, Sanjay Kumar Dhar, Vijay Kumar Sharma, (International Journal of Innovative Research in Medical Science, 2017)
We conducted an institutional based retrospective study on 141 uveitic patients treated at our center between Apr 2014 - Apr 2016 and analyzed the pattern of uveitis. A complete ophthalmologic examination was done in all patients. Relevant serological and radiological investigations were carried out based on clinical features to reach definitive diagnosis. Evaluations by concerned specialist were done as and when indicated. The main outcome measured included pattern of uveitis according to anatomical classification and etiology. Most patients were treated on outpatient basis. Classification of uveitis was done based on IUSG classification.[1] The final etiological diagnosis was done based on clinical features, lab investigations, and systemic evaluation. Male to female ratio was 3: 1. Mean age was 34.91. Anterior uveitis is the commonest type which constituted 80 cases (56.74%) followed by retinal vasculitis (19.15%), posterior uveitis 14 (9.93%), pan uveitis 11 (7.8%) pars planitis 6 (4.25%) and scleritis 2 (2.13%). Specific diagnosis could be made in 33 (37.5%) cases of anterior uveitis. Rest was idiopathic. Among 27 cases of vasculitis 4 were positive for tuberculosis and 1 patient was found to have sarcoidosis. Out of 141 cases, 24 (17.73%) had specific ocular disease and in 36 cases (24.82%) definite systemic association could be identified. More male preponderance is seen in our study, may be due to the clientele being the serving soldiers in the productive age group.